The Usage of Telecommunication Technologies in the Integration of Universities and Business - Sakhapov, Rustem Lukmanovich; Absalyamova, Svetlana Germanovna (International Journal of Advanced Corporate Learning (iJAC), 2014)
Abstract – Nowadays the world economy suffers a global innovation gap, which reveals itself in essential disproportions in innovative development of particular countries. The deep inequality is also observed in the sphere of innovations between various geographical regions. Unfortunately, Russia does not belong to the countries – leaders of the innovative development. The reasons of its underrun should be searched for in the sphere of organization of innovative process on the national level, in the state and condition of the national innovative system, and in the low effectiveness of the cooperation between universities and business. An active introduction of telecommunicational technologies can play a positive role in integration of education and business.